2012
DOI: 10.2478/v10007-012-0030-1
|View full text |Cite
|
Sign up to set email alerts
|

Semicarbazone – a versatile therapeutic pharmacophore for fragment based anticonvulsant drug design

Abstract: During the last fifteen years, semicarbazones have been extensively investigated for their anticonvulsant properties. 4-(4-Flurophenoxy) benzaldehyde semicarbazone (C0102862, V102862) was discovered as a lead molecule and is being developed as a potent antiepileptic drug, with maximal electroshock (MES) ED50 of i.p. 12.9 mg kg-1. In MES (oral screen), this compound has a protective index (PI = TD50/ED50 > 315) higher than carbamazepine (PI 101), phenytoin (PI > 21.6) and valproate (PI 2.17). The compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The positions and shapes of the peaks were dependent on the scan rate but the numbers of peaks remain same. The results were indicative of an irreversible two electron transfer to electro reduction of semicarbazone and thiosemicarbazone moiety [19][20][21][22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The positions and shapes of the peaks were dependent on the scan rate but the numbers of peaks remain same. The results were indicative of an irreversible two electron transfer to electro reduction of semicarbazone and thiosemicarbazone moiety [19][20][21][22][23][24][25] .…”
Section: Resultsmentioning
confidence: 99%
“…The product Amino(2-(N-hydroxy-3-isopropyl-2,6-difurylpiperidin-4-one-ylidene) hydrazinyl) methanol(3a) and Amino(2-(N-hydroxy-3-isopropyl-2,6-difurylpiperidin-4-oneylidene) hydrazinyl) methane thiol(3b) were screened for the antibacterial activity for eight test bacteria [21][22][23][24][25][26][27][28] . The bacterial strains used for inhibition study and the results were revealed in the table 5.…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low fluorescence intensity of isatin N ‐phenylsemicarbazone derivatives due to the predominant non‐radiative excited state deactivation, results of this study can be a useful supplement for better understanding of complex processes in solution of effective colorimetric sensors based on isatin N ‐phenylsemicarbazone. Moreover, because isatin semicarbazones are often biologically active, concept of associate/hydrazide/hydrazonol equilibrium in solution can help other researches in this field to deeply understand the structure–property and structure–biological activity relationships of some isatin semicarbazones. Structure of studied isatin N ‐phenylsemicarbazone E ‐isomers is depicted in Scheme .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, isatins are the synthetic precursors of some biologically important compounds 14,15 . Because of the continuing interest about isatin and its derivatives [16][17][18][19] , the present work was undertaken to test the solubility of isatin in different solvents at different temperatures and as a result, to evaluate different thermodynamic parameters. Further, various thermodynamic parameters have been evaluated from these solubility data.…”
Section: Introductionmentioning
confidence: 99%